2021
DOI: 10.3389/fpsyg.2021.690539
|View full text |Cite
|
Sign up to set email alerts
|

Can Psychosocial Intervention Suppress Testosterone and Triglycerides Among Women With Polycystic Ovary Syndrome? A Feasibility Trial

Abstract: Women with polycystic ovary syndrome (PCOS) suffer significant psychological distress, which may activate the hypothalamus-pituitary-ovary axis and further affect their physiological state. They often experience elevated levels of testosterone and triglycerides. Considering reports of psychological distress among women with PCOS, this study aimed to develop a psychosocial intervention to improve their emotional and physical health, particularly in Chinese society. This pilot study employed the Integrative Body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Among the 14 trials, nine trials were RCTs (12 citations) ( 34 45 ), four were single-arm trials ( 46 – 49 ) and one was a quasi-experimental trial ( 50 ). The distribution of trials across geographical locations included six trials (9 citations) conducted in India ( 34 37 , 39 , 44 , 46 , 47 , 49 ), four in the USA ( 40 , 42 , 45 , 48 ), and one each in China ( 41 ), Iran ( 50 ), Greece ( 38 ) and Slovenia ( 43 ). Refer to Table 1 for a summary of available evidence.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 14 trials, nine trials were RCTs (12 citations) ( 34 45 ), four were single-arm trials ( 46 – 49 ) and one was a quasi-experimental trial ( 50 ). The distribution of trials across geographical locations included six trials (9 citations) conducted in India ( 34 37 , 39 , 44 , 46 , 47 , 49 ), four in the USA ( 40 , 42 , 45 , 48 ), and one each in China ( 41 ), Iran ( 50 ), Greece ( 38 ) and Slovenia ( 43 ). Refer to Table 1 for a summary of available evidence.…”
Section: Resultsmentioning
confidence: 99%
“…A 2012 study [ 9 ] reported that higher HDL-C and lower LDL-C have a positive regulatory effect on depression and anxiety. In a 2021 study [ 5 ], the authors found that intervention in triglyceride level can effectively alleviate anxiety symptoms. A recently published animal experimental study also reported that eight weeks of an increased-fat diet effectively caused metabolic disorders, like obesity and hyperlipidemia, resulting in anxiety-like behavior in mice [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been considerable efforts to explore biological biomarkers related to and/or causing psychiatric disorders, with blood lipid being a potential etiological variable that has been quite extensively investigated. For example, previous studies indicated that high triglycerides (TG) quantity was connected to a high risk of major depressive disorder (MDD) [ 4 ], anxiety disorder [ 5 ], posttraumatic stress disorder (PTSD) [ 6 ], Alzheimer’s disease [ 7 ] and Schizophrenia [ 8 ]. However, other studies failed to prove such relationships [ 4 , 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Depending on the characteristics of populations in different regions and research definitions, the prevalence of PCOS varies from 8% to 13%. 4 PCOS not only affects women's reproductive health (infertility), while increasing the risk of long-term complications (diabetes, endometrial cancer, cardiovascular disease, and mood and eating disorders), [5][6][7][8][9][10] but also affects the health of their offspring. [11][12][13] At present, there is no effective cure for PCOS, and early and long-term management of the condition is needed to effectively reduce the impact of PCOS on both patients and their offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the characteristics of populations in different regions and research definitions, the prevalence of PCOS varies from 8% to 13% 4 . PCOS not only affects women's reproductive health (infertility), while increasing the risk of long‐term complications (diabetes, endometrial cancer, cardiovascular disease, and mood and eating disorders), 5–10 but also affects the health of their offspring 11–13 …”
Section: Introductionmentioning
confidence: 99%